The Impact of the Ontario Fertility Program on Duplicate Fertility Consultations - Assal, Angela (Healthc Policy, 2019)
OBJECTIVES: The Ontario Fertility Program (OFP) funds 5,000 annual in vitro fertilization (IVF) cycles. We hypothesized that after introduction of the OFP, there would be an increase in duplicate infertility consultations by patients attempting to increase chances at obtaining publicly funded IVF through enlisting at multiple fertility clinics. METHODS: This retrospective observational study included women eligible for healthcare services in Ontario from 2014 to 2016 and compared infertility consultations pre- and post-initiation of the OFP. RESULTS: Post-OFP, the average number of consultations per patient and the proportion of patients with more than one consult increased (1.04 vs. 1.05, p = 0.015 and 3.8% vs. 4.2%, p = 0.027, respectively). Total consultations for infertility increased from 24,565 to 27,714 post-OFP. The OFP had the largest impact in the Greater Toronto Area (GTA). CONCLUSION: The OFP resulted in a statistically significant increase in duplicate consultations, although unlikely to be of clinical relevance. The disproportionate impact seen in the GTA highlights the inequitable access to fertility care in Ontario.